2018
DOI: 10.1039/c8ra02582g
|View full text |Cite
|
Sign up to set email alerts
|

Morphologically controlled synthesis of ionic cesium iodide colloidal nanocrystals and electron beam-induced transformations

Abstract: Morphologically controlled synthesis of cesium iodide colloidal nanocrystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…We first synthesized the hexagonal CsBr NCs by hot‐injection. [ 41 ] Then the CsBr NCs could be post‐treated with Pb 2+ to achieve the controllable NRs (detailed experiment information is shown in the Experimental Section). The CsBr NCs were obtained for post‐treating by adjusting the reaction time, temperature and centrifugal speed.…”
Section: Resultsmentioning
confidence: 99%
“…We first synthesized the hexagonal CsBr NCs by hot‐injection. [ 41 ] Then the CsBr NCs could be post‐treated with Pb 2+ to achieve the controllable NRs (detailed experiment information is shown in the Experimental Section). The CsBr NCs were obtained for post‐treating by adjusting the reaction time, temperature and centrifugal speed.…”
Section: Resultsmentioning
confidence: 99%
“…[28] Fortunately, as with LHP, inorganic alkaline halide salt can also be synthesized as a state of nanocrystal colloidal solution, offering alkali metal cations, halogen anions, and ligand-rich liquid environment at mesoscopic scale in the meanwhile. [19,[29][30][31] In 2018, Manna et al reported a transformation from CsX (X = Cl, Br, I) nanocrystals to CsPbX 3 nanocrystals by cation exchange. [30,32] A possible reaction has been proposed: The reaction predicts that under appropriate conditions, such as heat, alkaline halide nanocrystals could release ligand-bonded ions into the environment as a result of its high surface energy as nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from chemical modification, the morphology, crystal structure, chemical composition, and electronic band structure of inorganic materials can be altered by bombarding solids with high-energy particles such as protons, electrons, and γ-radiation. , On irradiation, the energetic particles penetrate through the solid and the projectile energy of the energized particles is transferred to the atoms of the target material through their interaction with the subatomic particles . This process can lead to any of the following events in the material: localized heating, dislocation of the atoms, amorphization, , structural phase transitions, oxidation/reduction process, and mechanical changes .…”
Section: Introductionmentioning
confidence: 99%